A comparative study on susceptibility, course of parasitemia, and pattern of infection with Trypanosoma evansi between different laboratory animals. Issue 1 (1st January 2020) - Sadek, Al- Shaimaa M.
Abstract : This study investigated the susceptibility of eight different animal species (rat, mice, guinea pigs, hamsters, rabbits, sheep, goats, and chicken) experimentally infected with Trypanosoma evansi isolated from camels. In all laboratory animals, the number of trypanosomes was standardized according to the weight of the animal, and daily examination of the blood was conducted to assess the presence of trypanosomes to determine the prepatent period and the peak of parasitemia. Results suggested that mice and rats were the most susceptible laboratory animals to infection, whereas hamsters and guinea pigs displayed a certain degree of tolerance to infection. Rabbits exhibited a chronic course of infection, but the level of parasitemia was very low. In sheep and goats, trypanosomes were detectable only by subpassage to rats and mice, whereas all the chickens remained uninfected even with increasing doses of infection.